Sociodemographic and Psychosocial Determinants of Prenatal Exercise Participation: A Cross-Sectional Study - Solehati; Raden Maria Veronika Widiatrilupi (KHD Production, 2026)
Pregnancy exercise is a vital non-pharmacological intervention for preparing women physically and mentally for childbirth. Despite its proven clinical benefits, participation rates in prenatal exercise classes remain suboptimal in many community healthcare settings. This study aimed to analyze the sociodemographic and psychosocial factors associated with pregnant women's participation in pregnancy exercise classes at a private midwifery practice in Indonesia. A quantitative cross-sectional design was employed. The study population comprised pregnant women in their second and third trimesters. Using a total sampling technique, 30 respondents were selected. Data were collected using a structured questionnaire that assessed maternal age, education level, occupation, and family support. Bivariate analysis was conducted using the Chi-Square test to determine statistically significant relationships. The findings revealed that only 40% of respondents regularly participated in the exercise classes. Bivariate analysis demonstrated significant relationships between class participation and maternal age (p=0.03), educational attainment (p=0.008), and employment status (p=0.037). Younger, highly educated, and non-working mothers exhibited substantially higher attendance rates. Conversely, older age, lower education, and occupational demands presented significant barriers to routine engagement. Maternal age, education, and occupation are critical determinants of prenatal exercise participation. Midwives and healthcare policymakers must leverage these insights to design targeted, inclusive health promotion strategies and flexible scheduling to overcome sociodemographic barriers and optimize maternal health outcomes.